Weeds Predominant in Potato Fields: A Case of Southern Division, Kabale Municipality, Kabale District, South Western Uganda. - Akankwasa, Lowland (Kabale University, 2023)
The existence of weeds on potato crops could decrease the productivity of the crops, so that weed control efforts were absolutely necessary. The diversity of dominant weed types need-ed to be known so that weed control could be done correctly. This study aimed to make dominant weed mapping on potato cultivation in Southern Division Kabale Municipality. Two fields of Irish potato scattered at different altitude or topographic conditions were ran-domly selected in each village. At each field the weed samples were taken diagonally (5 times) for each plot of potato cropping using quadrants of size 0.5 m × 0.5 m. Field data was used to determine weed species, weed density, weed frequency, weed domination, im-portance value, summed dominance ratio, weed dry weight and species diversity index. The results showed that the dominant weed species in Central, Nyakambu, Mwanjari and Nya-kiharo were Galinsoga parviflora, Amaranthus spinosus, Drymaria vilosa and Cyperus ro-tundus, respectively. Weed diversity index ranged from 1.46 to 2.26. This study concluded that broad-leaved weeds are the dominant weed types in potato fields in the Southern Divi-sion of Kabale Municipality.